Research on characteristic model-based atmospheric duct interference control in TDD wireless communication system - Xiaoyun WANG; Wei DENG; Long ZHANG; Xin SU; Shizhuo ZHAO (Dianxin kexue)
Atmospheric duct interference is a seriousinternal interference of large-scale TDD wireless communication system according to specific meteorological conditions.The causes and classification of the atmospheric duct interference were analyzed firstly.Then a typical quantitative interference signal propagation model of inland and sea atmospheric duct were proposed and the power characteristics of massive interference sources in time domain and frequency domain were verified.The feature of the proposed model is based on a large number of data in real 4G/5G network environment, which is of great significance for the prediction and cancellation of atmospheric duct interference.Finally, four design principles were proposed for the frame structure and networking in TDD system to control atmospheric duct interference based on the characteristics of the proposed model.The verification in 5G network shows that the uplink interference drops more than 10 dB by the proposed interference control principles.It will also be instructive for the design of 6G system.